Study on Supply Chain Rearrangement to Improve Supply Chain Performance of Sambal Sauce in Company X Case Study using the Enterprise Architecture Design method that utilizes Industrial Revolution 4.0 Technology based on Hybrid Technology - Hermawan, Andri; Idris, Mohd Razif; Binti Mustaffa Bakry, Faridah (Jurnal Improsci, 2024)
Company X is a large enough producer of Sambal Sauce to supply Meatball traders in Indonesia. Many problems in this supply chain include the occurrence of unhealthy competition between internal networks, both between agents and other networks that intersect between supply regions, market prices are not uniform, the availability of field products is not maintained, the uncertainty of delivery from the previous supply from the Supply Chain, high Debts and Receivables from Distributors, the certainty of product delivery to the Supply Chain from Producers, The certainty and stability of the delivery of Sambal Sauce Raw Materials to the Factory, unstable quality of raw materials, and many other problems. Of course, this needs to be fixed immediately, considering that it will be a turning point for product returns if this problem continues. The following is a deeper study of what and why this happens, how to solve the problem, and concrete efforts to solve the problem analytically using the Enterprise Architecture Design method by utilizing Hybrid Technology-based Industrial Revolution 4.0 Technology.